Technology Enabled Permission Marketing Practices: Driving Indian Consumers Through Innovation (Trinity Journal of Management, IT & Media (TJMITM), 2013)
Consumers around the world are bombarded with too  many options of products which are either new or seems to  be new .Consumers, therefore feel that they are a part of  marketing arena where either the products or schemes  related to them are making life miserable. Permission  Marketing (PM), which emphasise on seeking permission  first and then dissemenation of marketing messages has  become the need of hour. PM practices which are  technology driven either by mobile technology or internet  technology give respite to consumers by allowing  permitted marketing messages. Present study is based on  secondary data which had been collected from various  sources like Book Reviews of book authored by Seth  Godin, Review Reports, Survey Reports of Telecom  Regulaory Authority of India (TRAI) , Marketing White  Book and various other reports.The data available in  various dissertations ,research papers and articles have  been also utilized by the accession of DELNET and  EBESCO. This paper will emphasise on how by using  mobile and inernet technology , Indian consumers can  make a better decision keeping their choice in consideration. This paper is useful for marketing professionals who are in the business of marketing of  various goods and services by highlighting the future  research directions in this bizarre area.
Keywords: Mobile; Internet; Permission Marketing; Technology; Innovation